2022
DOI: 10.1101/2022.09.30.22280585
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population-level risk factors related to measles case fatality: a conceptual framework based on expert consultation and literature review

Abstract: Introduction: A better understanding of population-level factors related to measles case fatality is needed to estimate measles mortality burden and impact of interventions such as vaccination. This study aimed to develop a conceptual framework of mechanisms associated with measles case fatality ratios (CFRs) and assess the scope of evidence available for related indicators in the published literature. Methods: Following expert consultation, we constructed a conceptual framework of mechanisms associated with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Previous work identified measles incidence and age to be critical covariates when assessing measles CFR. 3,5,7 We additionally selected covariates based on a systematic review and expert consultation 7 that identified five possible underlying mechanisms contributing to systematic increases or decreases in measles CFR (health system access and care seeking behaviours, health system quality, nutritional status, measles control and epidemiology, and risk of secondary infection) and related population-level indicators with evidence of an association with measles CFR (average household size, educational attainment, first-dose coverage of measles-containing vaccine (MCV1), human immunodeficiency virus (HIV) prevalence, level of health care availability, second-dose coverage of measles-containing vaccine (MCV2), stunting prevalence, surrounding conflict, travel time to nearest health care facility, under-five mortality rate, underweight prevalence, vitamin A deficiency prevalence, vitamin A treatment prevalence, and wasting prevalence).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous work identified measles incidence and age to be critical covariates when assessing measles CFR. 3,5,7 We additionally selected covariates based on a systematic review and expert consultation 7 that identified five possible underlying mechanisms contributing to systematic increases or decreases in measles CFR (health system access and care seeking behaviours, health system quality, nutritional status, measles control and epidemiology, and risk of secondary infection) and related population-level indicators with evidence of an association with measles CFR (average household size, educational attainment, first-dose coverage of measles-containing vaccine (MCV1), human immunodeficiency virus (HIV) prevalence, level of health care availability, second-dose coverage of measles-containing vaccine (MCV2), stunting prevalence, surrounding conflict, travel time to nearest health care facility, under-five mortality rate, underweight prevalence, vitamin A deficiency prevalence, vitamin A treatment prevalence, and wasting prevalence).…”
Section: Methodsmentioning
confidence: 99%
“…Then, in a second stage model, we used the same general model formula previously described, maintaining the spline knot locations identified in the first stage model, and fit our outcome of logit CFR to all data following age-splitting (Supplementary Information Section 3). To ensure the correct direction of association between each covariate and CFR, defined as the direction described previously 7 , we placed priors on each regression coefficient. We generated 1000 samples of the regression coefficients from their fitted joint posterior distribution and predicted country- and age-specific measles CFR in LMICs from 1990 to 2019.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations